Rewriting the History through the Standpoint of Margin: A Rereading of B.P. Koirala’s Atmabrittanta - Lamichhane, Yog Raj (Literary Studies, 2016)
Atmabrittanta is a unique and transcribed autobiography of B. P. Koirala - a thinker and a statesman. Rewriting the history from the standpoint of margin is the prime issue of this work. It includes mainly painful, romantic, adventurous and even terrible anecdotes of different people which took place for the establishment and reactivation of democracy and pitiless plot against it. Those events which were historically marginalized and excluded in history are included in Atmabrittanta. The interim impulse of truth and power as well as the formation of discourses are scrutinized through some selective happenings. B. P. Koirala highlights the contemporary marginal issues and illustrates how the ink of authority is abused to craft one-sided and monolithic history. In this way, the text becomes the common experience of general people beyond author’s journey of life and contradicts the mainstream history with full testimony of rebel. All these issues that walk off through the narrative make the autobiography more political than personal.